Improvement of the Mechanism for the Management of Innovation Activity in the Manufacturing Industry - Vitalii Nikolaevich Makoveev (Economic and Social Changes: Facts, Trends, Forecast, 2015)
The transition of Russia’s economy from raw materials exporting model of development to the innovation model is a national priority, since it contributes to intensive and sustainable economic growth and reduces economic dependence on external markets. GDP growth rate of 75–90% in the developed countries such as the USA, Japan, Germany, the UK, France, and also in the newly industrialized countries of Southeast Asia and China, is achieved due to the “progress of knowledge” – the intellectualization of the main production factors. Due to this fact, the increase in the standard of living in Russia, as well as overcoming its technological and economic lagging behind the more developed countries is possible only on the basis of the increase in productivity, enhancement of Russia’s competitiveness in international markets of innovative products, modernization and sustainable development of industrial enterprises through the creation of new innovation capabilities and the extensive utilization of that which have already been accumulated. The manufacturing industry is a powerful driving force of innovation economic development, since this sector concentrates the main production of the most technologically sophisticated and knowledgeintensive products with high added value. However, in the process of market transformations the products of domestic manufacturing enterprises have become much less competitive on international markets. There is a steady tendency toward the growth of imports and decrease of exports of enterprises of this sector. In this regard, the article identifies the factors that have the greatest influence on the development of innovation activities in the manufacturing industry. The author builds a multivariate regression model that determines the degree of influence of various socio-economic factors on the level of development of innovation activity in manufacturing. The paper proposes an organizational-economic mechanism for enhancing innovation in the manufacturing industry and increasing the competitiveness of the products of enterprises in this sector